Lack of creatine in muscle and brain in an adult with GAMT deficiency - Schulze, Andreas; Bachert, Peter; Schlemmer, Heinz-Peter; Harting, Inga; Polster, Tilman; Salomons, Gajja S.; Verhoeven, Nanda M.; Jakobs, Cornelis; Fowler, Brian; Hoffmann, Georg F.; Mayatepek, Ertan (Annals of neurology, 2003)
Guanidinoacetate methyltransferase deficiency, which so far has been exclusively detected in children, was diagnosed in a 26-year-old man. The full-blown spectrum of clinical symptoms already had been present since infancy without progression of symptoms during adolescence. Cranial magnetic resonance imaging showed normal findings. Ophthalmological examination showed no retinal changes. Besides creatine deficiency in the brain, a distinct lack of phosphocreatine in skeletal muscle was proved by 31P magnetic resonance spectroscopy. Creatine substitution combined with a guanidinoacetate-lowering diet introduced first at the age of 26 years was shown to be effective by an impressive improvement of epileptic seizures, mental capabilities, and general behavior and by normalization of the 31P spectrum in the skeletal muscle.
Gesehen am 22.12.2020